2017
DOI: 10.5751/es-09077-220138
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and obstacles for rangeland conservation in San Diego County, California, USA

Abstract: ABSTRACT. Working landscapes such as rangelands are increasingly recognized as having high conservation value, providing a variety of ecosystem services, including food, fiber, habitat, recreation, open space, carbon storage, and water, in addition to a broad range of social benefits. However, conversion of rangelands to other land uses has been prevalent throughout the western United States, leading to greater attention in the conservation community to the importance of collaborating with private landowners. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Interviews confirmed our a priori understanding that, despite having commonalities with rangeland elsewhere (e.g., Farley et al ), ranching landscapes in the Calgary region represent a unique cultural landscape that incorporates interacting material features, land‐use practices, and socio‐cultural characteristics. Not all participants felt that ranching landscapes exist as distinct entities, given the mixed nature of many agricultural operations in the Calgary area.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Interviews confirmed our a priori understanding that, despite having commonalities with rangeland elsewhere (e.g., Farley et al ), ranching landscapes in the Calgary region represent a unique cultural landscape that incorporates interacting material features, land‐use practices, and socio‐cultural characteristics. Not all participants felt that ranching landscapes exist as distinct entities, given the mixed nature of many agricultural operations in the Calgary area.…”
Section: Resultssupporting
confidence: 73%
“…It can be particularly important in encouraging landscape stewardship, as other studies have found (Farmer et al ; Hurley ; Winthrop ; Plieninger et al ). The implication of this for land‐use planning is that, to echo Kerselaers et al (, 205), strategies and solutions to encourage good land stewardship need to “match the different values at play.” More non‐economic, deliberative techniques are needed to involve private landowners in eliciting and assessing both what is important to protect, and what is most vulnerable (Milcu et al ; Iniesta‐Arandia et al ; Plieninger et al ; Farley et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that it is possible to simultaneously pursue environmental and human values and may be applicable to other regions where biodiversity richness and high fire risk overlap. https://www.ecologyandsociety.org/vol23/iss2/art3/ The second article in this theme by Farley et al (2017) is also located in San Diego County, California, USA, and focuses on rangelands. Based on geographic information system analyses of land use changes and 13 in-depth interviews with ranchers, the authors investigated the rate of rangeland conversion and participation in rangeland conservation programs.…”
Section: Land-cover and Other Environmental Changesmentioning
confidence: 99%
“…To further enhance collaboration, it is imperative that political support be obtained at multiple levels, including national, provincial, and district and local government agencies (1.1, Table 1). Ultimately, the efficiency of private and public land conservation may be improved through better integration (SANBI, 2017;Farley et al, 2017).…”
Section: Table 4 Summary Of Recommenda Onsmentioning
confidence: 99%